Formation of teaching content in E-learning - Marinković, Renata (Array, 2011)
The greatest contribution of the introduction of E-learning into education is the stimulation of active learning. E-learning with the appropriate programme support in specific phases of the educational process contributes to the individualization of education and stimulates the pupils’ activity. The attention of this paper is focused on the formation of educational content in the E-learning systems. Entering the activities of the subject they have enrolled, the third-grade elementary school pupils analyzed the educational materials, solved tasks and used educational tools for mutual cooperation and communication in the MOODLE and CoLaB Tutor systems. By quality application of the mentioned systems in education results were achieved that pointed to the interest and excellent dispositions of this age group for specific forms of learning.